SUNAN KALIJAGA'S PHILOSOPHICAL THINKING IS RELEVANT FOR STRENGTHENING CHARACTER EDUCATION IN INDONESIA - Arqom Kuswanjono; Heri Santoso; Kusuma Putri; Dela Khoirul Ainia (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
The aims of this study are to explore the philosophical thoughts of Sunan Kalijaga and, to inventory Sunan Kalijaga's philosophical thoughts that affect reinforcement character education in Indonesia. The method in this research is the historical factual character, which is to examine the character's thoughts on current actual problems with the help of the character's literature study. The results are reinforcement character education in Indonesia through the philosophical thinking of Sunan Kalijaga and, an education model characterized by Indonesia. Character education based on the philosophical values of these figures will lay the foundation for values to build strength and a basis for legitimacy for the practice of life, whether carried out by students at school or in everyday life. With the philosophical values of figures in character education, it will color the face of education in Indonesia to start building a non-western educational paradigm based on the embryo of national identity, namely the Nusantara.